2009
DOI: 10.1007/s00464-008-0274-5
|View full text |Cite
|
Sign up to set email alerts
|

Utility of endoscopy in patients with incidental gastrointestinal luminal wall thickening detected with CT

Abstract: Endoscopic study is useful in patients with IGILWT. More than one-third of patients with IGILWT have a significant finding by endoscopic evaluation, mainly cancer. Absence of GI symptoms/signs, age or gender are not valid criteria to decide about further endoscopic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 8 publications
0
21
1
1
Order By: Relevance
“…This includes a study by Tellez-Avilla et al in 2009. 5 Although only 12/31 asymptomatic patients with incidental CT findings of BWT (38.8%) had abnormalities on endoscopy, the authors still recommended this investigation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes a study by Tellez-Avilla et al in 2009. 5 Although only 12/31 asymptomatic patients with incidental CT findings of BWT (38.8%) had abnormalities on endoscopy, the authors still recommended this investigation.…”
Section: Methodsmentioning
confidence: 99%
“…3 Tellez-Avilla et al found that 29% of asymptomatic patients presenting with GI wall thickening (including stomach and duodenum) had cancer on endoscopy. 5 Bleibel et al showed that 18% of patients with incidental CT findings of GI wall thickening had a malignancy on endoscopy. 7 In that study, all the patients diagnosed with cancer were over 50 years of age and the authors therefore suggested the use of follow-up endoscopy in patients above this age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonic wall thickening is frequently encountered at CT and may be related to normal variants such as diverticular disease, inflammatory conditions, and neoplastic disease [1]. Because no uniform guidance exists, debate surrounds the clinical significance of bowel wall thickening found at CT when demonstrated by both abdominopelvic CT (APCT) or CT colonography (CTC) [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…Son yıllarda BBT'nin sık kullanılması sonucu barsak duvar kalınlaşması (BDK) sık karşılaşılan bir bulgu olmuştur. 2 Bu bulgu normalin varyantı olabileceği gibi, benign veya malign hastalıklarda da karşımıza çıkabilir. Bu nedenle etiyolojik faktörleri belirlemek için, kolonoskopi gibi ileri endoskopik incelemeler yapılabilir.…”
unclassified